2014
DOI: 10.1093/gbe/evu021
|View full text |Cite
|
Sign up to set email alerts
|

Paternally Transmitted Mitochondria Express a New Gene of Potential Viral Origin

Abstract: Mitochondrial ORFans (open reading frames having no detectable homology and with unknown function) were discovered in bivalve molluscs with doubly uniparental inheritance (DUI) of mitochondria. In these animals, two mitochondrial lineages are present, one transmitted through eggs (F-type), the other through sperm (M-type), each showing a specific ORFan. In this study, we used in situ hybridization and immunocytochemistry to provide evidence for the expression of Ruditapes philippinarum male-specific ORFan (orf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 65 publications
(107 reference statements)
6
77
1
2
Order By: Relevance
“…Their functions are still unknown, although the presence of gene products in the nucleus indicates that they are not involved in ATP production, like other typical mtDNAencoded proteins (Breton et al 2011(Breton et al , 2014Milani et al 2014). An initial hypothesis proposed that these genes may play a role in sex determination because of the observation that gonochorism (i.e., separate male and female sexes) in freshwater bivalves is absolutely correlated with the presence of DUI and these novel sex-specific proteins whereas closely related hermaphroditic species lack the M mtDNA (i.e., possess SMI) and have macromutations in the F-orf in their F mtDNAs (Breton et al 2011).…”
Section: Doubly Uniparental Inheritancementioning
confidence: 99%
“…Their functions are still unknown, although the presence of gene products in the nucleus indicates that they are not involved in ATP production, like other typical mtDNAencoded proteins (Breton et al 2011(Breton et al , 2014Milani et al 2014). An initial hypothesis proposed that these genes may play a role in sex determination because of the observation that gonochorism (i.e., separate male and female sexes) in freshwater bivalves is absolutely correlated with the presence of DUI and these novel sex-specific proteins whereas closely related hermaphroditic species lack the M mtDNA (i.e., possess SMI) and have macromutations in the F-orf in their F mtDNAs (Breton et al 2011).…”
Section: Doubly Uniparental Inheritancementioning
confidence: 99%
“…The other groups in which species with DUI have been found are the orders Mytiloida (family Mytilidae) (Hoeh, Blakley & Brown, 1991; Skibinski, Gallagher & Beynon, 1994; Zouros et al, 1994a; Zouros et al, 1994b; Passamonti, 2007), Veneroida (families Arcticidae, Donacidae, Mactridae, Solenidae, Veneridae) (Theologidis et al, 2008; Plazzi, 2015; DĂ©gletagne, Abele & Held, 2016), and Nuculanoida (family Nuculanidae), an order belonging to the most basal protobranch bivalve lineage (Boyle & Etter, 2013). It is still unsettled whether DUI has a single origin followed by its loss in several bivalve lineages or whether it has multiple and independent origins (Hoeh et al, 1996; Theologidis et al, 2008; Zouros, 2013; Milani et al, 2014). To disentangle these two possibilities, we must expand taxonomic sampling in a comprehensive manner.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, both mitochondrial types have acquired new genes (55)(56)(57), confirming that animal mitochondrial genomes are capable of evolving novelty. Little is known about the function of these novel genes, although recent studies have shown that they are transcribed and translated into proteins (58). Although they have no clear homologs, it has been suggested that at least one of the novel genes may have a viral origin (55,57,58).…”
mentioning
confidence: 99%
“…Little is known about the function of these novel genes, although recent studies have shown that they are transcribed and translated into proteins (58). Although they have no clear homologs, it has been suggested that at least one of the novel genes may have a viral origin (55,57,58). Understanding the function of these novel genes will not only gain insight into the mechanism of doubly uniparental inheritance, but it may also shed light on how sex itself is determined in bivalves, as this is not yet known.…”
mentioning
confidence: 99%